Determinants of patient‐reported xerostomia among long‐term oropharyngeal cancer survivors. Issue 23 (6th August 2021) - Aggarwal, Puja; Hutcheson, Katherine A.; Garden, Adam S.; Mott, Frank E.; Lu, Charles; Goepfert, Ryan P.; Fuller, Clifton D.; Lai, Stephen Y.; Gunn, G. Brandon; Chambers, Mark S.; Sturgis, Erich M.; Hanna, Ehab Y.; et al.
Abstract : Background: This study was conducted to identify clinicodemographic risk factors for xerostomia among long‐term oropharyngeal cancer (OPC) survivors. Methods: This cross‐sectional study included 906 disease‐free, adult OPC survivors with a median survival duration at the time of survey of 6 years (range, 1‐16 years); self‐reported xerostomia scores were available for 877 participants. Study participants had completed curative treatment between January 2000 and December 2013 and responded to a survey administered from September 2015 to July 2016. The primary outcome variable was cancer patient–reported xerostomia measured with the MD Anderson Symptom Inventory Head and Neck Cancer Module. Clinicodemographic risk factors for moderate to severe xerostomia were identified via multivariable logistic regression. Results: Moderate to severe xerostomia was reported by 343 of the respondents (39.1%). Female sex (odds ratio [OR], 1.82; 95% CI, 1.22‐2.71; P = .003; Bayesian false‐discovery probability [BFDP] = 0.568), high school or lower education (OR, 1.73; 95% CI, 1.19‐2.52; P = .004; BFDP = 0.636), and current cigarette smoking at the time of survey (OR, 2.56; 95% CI, 1.19‐5.47; P = .016; BFDP = 0.800) were risk factors for moderate to severe xerostomia, and bilateral intensity‐modulated radiotherapy (IMRT) combined with proton therapy and ipsilateral IMRT were protective. Conclusions: In this large xerostomia study, modern radiotherapy was a protective factor, and continued cigarette smoking at the time of survey, female sex, and high school or lower education were identified as other contributing risk factors associated with moderate to severe xerostomia. Importantly, these findings need to be confirmed in prospective studies. These results can inform future research and targeted patient‐centered interventions to monitor and manage radiation therapy–associated xerostomia and preserve quality of life among patients with OPC. Abstract : Xerostomia is a common cancer treatment–associated oral morbidity that can contribute to increased patient suffering and poorer overall quality of life among patients with head and neck cancer. In the current study, modern radiotherapy is a protective factor, and continued cigarette smoking at the time of survey, female sex, and high school or lower education are identified as other contributing risk factors associated with moderate to severe xerostomia. Importantly, these findings need to be confirmed in prospective studies.